A Study of Persona Archetype in Rumi`s Masnavi - Jafarzadeh, Maryam; Hosseini, Zeinab Sheik (Mediterranean Journal of Social Sciences, 2012)
An Archetype describes all repeated images motifs and patterns in myths and literature which evoke a similar concept to awide group of human beings and cultures during different ages. Carl Gustav Jung who got a psychological aspect to this expressed thatone of the most famous kinds of this chiefly patterns in his psychology is Persona .In opinion`s Jung Persona is a compatible style ofevery one with world or it is a way that every one adjusts his/her treatment to world .Persona shows us in manner that we want toappear in society so that it is possible that it doesn`t compare to our real personality .It uses to conceal feelings and real thoughts.Persona contains mean of lie ,suspicion or meaningless. In this present article moreover was approached Persona`s conception , weconsidered some examples in Masnavi. According to this study Rumi has expressed different performance of Persona in different story.Persona was showed in form of humans that they conceal their real personality Persona or they lie and they covered their personalityunder their deception. The writer`s rights are similar. The names are according to alphabet letters